Effects of mGluR5 Antagonists on Parkinson's Patients With L-Dopa-Induced Dyskinesia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Wang, Wen-Wen; Zhang, Xing-Ru; Zhang, Zeng-Rui; Wang, Xin-Shi; Chen, Jie; Chen, Si-Yan; Xie, Cheng-Long (Frontiers in Aging Neuroscience, 2018)
Background: Modulation of Metabotropic glutamate receptor 5 (mGluR5) may be a novel therapeutic approach to manage Parkinson’s disease (PD) Patients with L-dopa-induced dyskinesia (LID). Objectives: The objective of this meta-analysis was to evaluate the effects of mGluR5 antagonists for the treatment of LID patients. Methods: Several electronic databases were consulted up to July 30, 2017. Randomized clinical trials (RCTs) that compared mGluR5 antagonists versus placebo in LID patients were included. Pooled weighted mean difference (WMD) with 95% confidence intervals (CIs) were calculated using random-effects models. Results: Nine trials including 776 patients met all inclusion criteria. We pooled the whole data and found apparent difference between mGluR5 antagonists and placebo in terms of mAIMS (p=0.010). However, there was no signiﬁcant improvements on antidyskinetic in terms of LFADLDS (p=0.42) and UPDRS Part Ⅳ (p=0.20). Meanwhile, the effect size of UPDRS part Ⅲ was similar in mGluR5 antagonist groups with in placebo groups (p=0.25). Adverse events incidence was higher with mGluR5 antagonists than with placebo, especially at the expense of increased dizziness (16.3% vs 4.3%), visual hallucination (10.1% vs 1.1%), or fatigue (10.1% vs 4.8%). Conclusions: mGluR5 antagonists had a greater treatment effect on the mAIMS in LID patients, however, there was no improvements on antidyskinetic in terms of LFADLDS and UPDRS Part Ⅳ compared with placebo. According to these results, we unable to recommend mGluR5 antagonists for the routine treatment of LID patients right now.